Post‐transcriptional regulation of the tumor suppressor miR‐139‐5p and a network of miR‐139‐5p‐mediated mRNA interactions in colorectal cancer. (15th July 2014) - Shen, Ke; Mao, Rurong; Ma, Li; Li, Yueqi; Qiu, Yanyan; Cui, Daling; Le, Vanminh; Yin, Peihao; Ni, Lei; Liu, Jianwen
<x xml:space="preserve">Abstract</x> MicroRNAs play key roles in many biological processes, and are frequently dysregulated in tumor cells. However, there are few studies on how microRNAs are dysregulated. miR‐139‐5p, an important tumor suppressor, is often underexpressed in gastrointestinal cancer cells. Here, we describe post‐transcriptional regulation of this intronic microRNA in human colorectal cancer. miR‐139‐5p is expressed independently of its overexpressed host gene PDE2A in colorectal cancer tissues and cell lines. The miR‐139‐5p target genes IGF1R, ROCK2 and RAP1B exert regulatory effects on the miR‐139‐5p expression level, relying on their ability to compete for miR‐139‐5p binding. These overexpressed target genes also regulate each others' protein levels through 3′‐UTRs, thus regulating tumor cell growth and motility properties. Our study provides a mechanistic, experimentally validated rationale for intronic microRNA dysregulation in colorectal cancer, revealing novel oncogenic roles of IGF1R, ROCK2 and RAP1B 3′‐UTRs.